Some Aspects of Collaboration in Inclusive Education – Teachers’ Experiences - Dejana Bouillet (Center for Educational Policy Studies Journal)
The main aim of the present article is to analyse some aspects of collaboration in inclusive educational practice in Croatian schools by analysing teachers’ experiences. Special attention is devoted to the professional support resources available to teachers, as well as to teachers’ views on the content and usefulness of the professional support they utilise. The article presents partial results of a larger research project regarding various components of inclusive practice in Croatian primary schools, organised at the Faculty of Teacher Education in Zagreb. A total of 69 primary school teachers were interviewed regarding the elements of inclusive practices in their own schools. Each teacher also completed a short questionnaire about their opinions on elements that weaken inclusive practices in their school, as well as on some general data about schools. The  data obtained were analysed on both the qualitative and the quantitative levels. The results suggest that, at the present time, collaboration in Croatian schools is not well organised and defined. It is shown that only a relatively small number of various professionals who could support teachers and students in inclusive processes work in schools. Furthermore, it is established that schools do not compensate for this problem with stronger collaboration between schools and professionals in local communities. Teachers would like to receive more specific advice, as well as more concrete assistance in the education of students with disabilities. The author concludes that a better conceptualisation of collaboration between schools and local communities is needed (especially a higher level of team work). This would certainly contribute to improving the quality of inclusive education in Croatian schools.